2017
DOI: 10.1182/blood-2017-02-770479
|View full text |Cite
|
Sign up to set email alerts
|

Circulating soluble P-selectin must dimerize to promote inflammation and coagulation in mice

Abstract: Leukocyte adhesion to P-selectin on activated platelets and endothelial cells induces shedding of the P-selectin ectodomain into the circulation. Plasma soluble P-selectin (sP-selectin) is elevated threefold to fourfold in patients with cardiovascular disease. Circulating sP-selectin is thought to trigger signaling in leukocytes that directly contributes to inflammation and thrombosis. However, sP-selectin likely circulates as a monomer, and in vitro studies suggest that sP-selectin must dimerize to induce sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 42 publications
2
73
0
Order By: Relevance
“…In a more recent study presented as an abstract venetoclax was combined with the hypomethylating agent azacytidine for elderly patients with AML. This small study revealed very encouraging response rates with an 85% remission rate [66]. The final results of this study are pending at this time.…”
Section: Targeting Mitochondrial Apoptotic Pathwaymentioning
confidence: 88%
“…In a more recent study presented as an abstract venetoclax was combined with the hypomethylating agent azacytidine for elderly patients with AML. This small study revealed very encouraging response rates with an 85% remission rate [66]. The final results of this study are pending at this time.…”
Section: Targeting Mitochondrial Apoptotic Pathwaymentioning
confidence: 88%
“…Among the biomarkers of inflammation and cardiovascular disease, soluble P-selectin was the only one to significantly correlated with S-SMase. Circulating soluble P-selectin is thought to trigger signaling in leucocytes that directly contributes to inflammation and thrombosis, and it is elevated in patients with cardiovascular diseases [12]. Soluble P-selectin has also been found to correlate with disease activity in RA patients with thrombocytosis [13].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with RA and control subjects participated in studies of inflammation and cardiovascular disease at Vanderbilt University Medical Center. Patients with RA met previously described inclusion and exclusion criteria and were studied between 2009 and 2011 as part of the baseline visit of a study of the anti-inflammatory effects of pioglitazone [12]. The control subjects were studied between 2013 and 2014 as part of a cardiac magnetic resonance imaging study, unpublished.…”
Section: Methodsmentioning
confidence: 99%
“…The data represent the mean 6 SEM from 5 experiments, with 5 mice in each experimental group. 38 Because monomeric soluble P-selectin does not signal, 48 we used oligomeric P-selectin isolated from human platelets. As control for mAbs KIM127 and MEM148, we used mAb IB4, which binds equivalently to nonactivated and activated b2 integrins.…”
Section: Selectins and Chemokines Cooperatively Activate B2 Integrinsmentioning
confidence: 99%